การศึกษาลักษณะจิตบริการในการปฏิบัติงานของพยาบาลวิชาชีพ โรงพยาบาลเอกชน - มรกต เหลืองอำนวยศิริ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The purpose of this research was to study of service orientation of professional nurses, private hospitals. Ethnographic Delphi Future Research (EDFR) technique was used to collect data. Participants were 20 experts consisting of 7 experts of nursing administration, 7 experts of academic nursing administration and 6 experts of nursing practice. The EDFR technique consisted of 3 steps: Step 1, all experts were interviewed about service orientation of professional nurses. Step 2, interviewed data were analyzed for developing a questionnaire and sent to prior experts for their opinion. Step 3, questionnaire items were analyzed for mean and interquartile range and then sent back to experts for their opinion’s confirmation. Major findings from the research of service orientation of professional nurses, private hospitals comprised of 3 major dimensions as follows : 1. Good attitude toward service delivery including 4 sub-characteristics: 1.1 Positively thinking to provide the service 1.2 Having service mind 1.3 Understanding the nature of clients 1.4 Understanding service expectations and needs of clients 2. Characteristics of professional nurses 2.1 Impressive personality 2.2 Managerial ability 3. Responsibility 3.1 Professional responsibility 3.2 Organizational responsibility 3.3 Societal & Environmental responsibility.